Firm heterogeneity in food safety provision: Evidence from aflatoxin tests in Kenya - Moser, Christine; Hoffmann, Vivian (International Food Policy Research Institute, 2015)
The lack of a reliably safe food supply in developing countries imposes major costs on both public health and market performance. This paper addresses the question of whether and why food processing firms voluntarily invest in food safety in the absence of effective regulatory enforcement. Using data from more than 900 maize flour samples representing 23 distinct brands in eastern and central Kenya, we explore the relationship between price, brand, and aflatoxin contamination. Aflatoxin is a toxin common in maize, groundnuts, and other crops around the world; and although it is unobservable to the consumer, it may be correlated with other quality characteristics. We find a strong negative correlation between price and contamination rates, which is consistent with certain brands investing more in quality to avoid loss of reputational capital.